Implementasi Peraturan Pemerintah Nomor 11 Tahun 2017 JO Peraturan Pemerintah Nomor 17 Tahun 2020 Tentang Manajemen PNS dalam Pengembangan Kompetensi ASN pada Badan Pengembangan Sumber Daya Manusia Provinsi Sumatera Utara - Ramal Ramal; Isnaini Isnaini; Budi Hartono (Mahesa Research Center, 2022)
The purpose of this paper is to describe the implementation and the factors that support and hinder Government Regulation Number 11 of 2017 concerning Civil Servant Management in developing ASN competencies at the Office of the Human Resources Development Agency of North Sumatra Province. The type of research used is qualitative to answer the existing problems. The data analysis of this research was carried out by means of data reduction; Presentation of data and drawing conclusions or verification. The results of the research found that the implementation was not optimal, namely: Communication was not optimal because not all information was given to employees; Human Resources are still lacking and the level of awareness about PNS Management is still lacking; Disposition of employee responsibilities is still very low in carrying out their work; Bureaucratic Structure Coordination of employees is not good because employee awareness in improving competencies related to PNS Management still needs to be further improved. The inhibiting factors for the implementation of Government Regulation Number 11 of 2017 concerning Civil Servant Management in developing ASN competence at the Office of the Human Resources Development Agency of North Sumatra Province such as Not all information being conveyed, Human resources are considered to be not good, some employees are less responsible for coordination between employees, there is still a lack optimal.